Investigation of the mechanical properties of Al-SiC MMC fabricated with different particle size - Muhamad Faqihiddin Syah, Muhamad Khalil (2016)
Silicon carbide particle reinforced aluminum matrix (Al) composites have been developed over past few decades, owing to their excellent properties like lightweight, high elastic modulus and wear resistance. Thus, the silicon carbide (SiC) particle reinforced Al composites are expected to have many applications in aerospace, aircraft, automobile and electronic industries. In this study, aluminum metal matrix composites (AMC) containing different particle size of reinforcement particles were prepared by using powder metallurgy method. The main steps in powder metallurgy are blending, compacting and sintering. The experiments were performed on micro and nano size particles of silicon carbide powder in the composite. The study presents the results of experimental investigation on mechanical behavior of silicon carbide particle reinforced aluminum matrix. The influence of MMC micro and nano particles on the mechanical behavior was examined. The hardness and microstructure was studied. Optical Metallurgical Microscope was used to characterize the composites. The hardness was measured by vicker micro hardness testing machine as per the ASTM E384. The microstructure observation shows better distribution of particles in case of nano particles as compared to micro particles. The overall results showed that the MMC reinforced with SiC nano particles exhibited better mechanical properties then MMC reinforced with micro particles.